Structural reform in New Zealand: A review - Peter Redward (Bank of Finland, 1996)
This paper discusses the reasons for the change in economic policy direction adopted in New Zealand in 1984.The paper briefly outlines the economic history of New Zealand in the period from the early 1970's to 1996.The ultimate test of the success of the economic reforms is whether they have increased the growth rate of potential per capita output in the economy. I discuss the evidence on this hypothesis and conclude that the evidence does support the hypothesis of a structural change in this measure.Five of the major areas of reform are discussed, these areas are goods, capital and labour market liberalisation and the fiscal and monetary policy framework adopted in New Zealand.
URN:NBN:fi:bof-20140807612
Keywords: 330; economic policy reform; New Zealand